2018
DOI: 10.1021/acsomega.8b00582
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product-Based 1,2,3-Triazole/Sulfonate Analogues as Potential Chemotherapeutic Agents for Bacterial Infections

Abstract: Despite the vast availability of antibiotics, bacterial infections remain a leading cause of death worldwide. In an effort to enhance the armamentarium against resistant bacterial strains, 1,2,3-triazole (5a–x) and sulfonate (7a–j) analogues of natural bioactive precursors were designed and synthesized. Preliminary screening against two Gram-positive (Streptococcus pneumoniae and Enterococcus faecalis) and four Gram-negative bacterial strains (Pseudomonas aeruginosa, Salmonella enterica, Klebsiella pneumoniae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…Results showed nontoxic behaviour towards the larvae viability. Moreover, the hemocyte density of larvae treated with tested compounds was not significantly affected if compared to untreated ones [95].…”
Section: In Vivo Toxicity Screeningmentioning
confidence: 84%
See 1 more Smart Citation
“…Results showed nontoxic behaviour towards the larvae viability. Moreover, the hemocyte density of larvae treated with tested compounds was not significantly affected if compared to untreated ones [95].…”
Section: In Vivo Toxicity Screeningmentioning
confidence: 84%
“…The in vivo toxicity assay using G. mellonella was performed on two triazole analogues (one derived from carvacrol and the other derived from 2-hydroxy 1,4-naphthoquinone) bearing carboxylic acid, which had previously been tested for their antibacterial activity in vitro [95]. Results showed nontoxic behaviour towards the larvae viability.…”
Section: In Vivo Toxicity Screeningmentioning
confidence: 99%
“…31.25 mg mL À1 for C. albicans. At predetermined time periods (0, 2,4,6,8,10,12,14,16,18,20,22, and 24 h) aer incubation with agitation at 37 C, 1 mL aliquot to each sample was removed from the conical ask and growth was measured turbidometrically at 600 nm using Thermo Multiskan spectrophotometer. Optical density (O.D.)…”
Section: Biologymentioning
confidence: 99%
“…In our continuous efforts to design biologically active heterocycles, [12][13][14][15][16][17] we hypothesized albaconazole as a model for preparation of 1,2,3-triazole derivatives of quinazolin-4(3H)-one (5a-q and 6a-q) and studied their antifungal properties. Further, single crystal X-ray study of compounds 2 and 5c has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Among the broad range of privileged structures, triazole represents one of the most prominent classes of N-heterocyclic scaffolds for novel synthetic drug discovery due to its broad range of pharmacological and biological activities (Jagdish et al, 2013;Kantheti et al, 2015;Nocentini et al, 2016;Aneja et al, 2018). Thought the triazole moiety has not been found in natural products, the development of efficient and straightforward methods for the preparation of triazole derivatives has greatly increased over the last two decades.…”
Section: Introductionmentioning
confidence: 99%